Influence of particle shape on aggregate mixture's performance: DEM results. Issue 2 (17th February 2019) - Zhou, Changhong; Zhang, Miaomiao; Li, Yuhua; Lu, Jiale; Chen, Jingyun
Abstract : In order to study the effects of aggregate shape on the strength of mixtures, the glue-sphered ellipsoid particles were used to create cylinder samples, and triaxial tests were simulated using the discrete element method. This paper discussed (a) how to create ellipsoid aggregates by glued spheres and control its size; (b) how to simulate the triaxial performance of hot-mix asphalt (HMA) skeleton; and (c) how to choose coarse aggregates for HMA according to shape factors. Through computation, a nephogram of triaxial strength varying with shape factors Flatness and Elongation was finally obtained. The results showed that cubical and part of rod aggregate work much better in strength than others, which were proved to be consistent with that of experimental results.